2015
DOI: 10.14800/ics.930
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume is a Significant Biomarker in the Differential Diagnosis of Acute Appendicitis

Abstract: In order to reduce negative appendectomy (NA) rate, red cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV) were investigated. But, their combined role on the differential diagnosis of acute appendicitis (AA) with a control group of NA have not been established. A total of 530 patients who underwent appendectomy with the pre-diagnosis of AA were retrospectively analyzed and divided into two groups: 1) 469 AA, and 2) 61 NA. Diagnostic value of statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…When MPV and PDW used for the diagnosis of acute appendicitis, different results were obtained. In some studies, it was stated that these values increase, while others decrease or do not differ [21][22][23][24]. In our study, we found that MPV value increased and PDW value decreased in patients with AA.…”
Section: Discussionsupporting
confidence: 54%
“…When MPV and PDW used for the diagnosis of acute appendicitis, different results were obtained. In some studies, it was stated that these values increase, while others decrease or do not differ [21][22][23][24]. In our study, we found that MPV value increased and PDW value decreased in patients with AA.…”
Section: Discussionsupporting
confidence: 54%
“…The RDW in our study was found to be 14.71±1.64, which was not significant (i.e., p=0.442 and p>0.05). Similar results were observed in the other studies conducted by Aktimur et al 1 and Tanrikulu et al 21 . However, it was noted that RDW was elevated in the perforated group when compared to the acute group, similar to the study by Boshnak et al 4 , which shows the high-grade inflammatory pathology of perforated appendicitis, and thus can be used as a predictive indicator.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were observed in the other studies conducted by Aktimur etal. 1 and Tanrikulu etal. 21 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations